An assessment of use of traditional medicine in pregnacy and associated factors among black South African women delivering in Bertha Gxowa Hospital - Mkize, Gugulethu Thokozani (My University, 2015)
INTRODUCTION: Black South African women use traditional medicines during pregnancy. Data on the extent of women‟s use of these is limited. Research has reported that some traditional medicines used in pregnancy may have negative pregnancy outcomes. The aim of the study was to determine the prevalence of traditional medicine use during pregnancy, the types used and factors associated with use amongst black South African women delivering in Bertha Gxowa hospital. METHODS: A cross sectional study was done on Black South African patients admitted in the post natal ward of Bertha Gxowa in May 2012 to June 2012. Women were interviewed by the researcher using a structured questionnaire. Data collected included demographic and obstetrical factors, prevalence of use of traditional medicines in pregnancy, the types of traditional medicines used and the reasons for their use. Information on knowledge of and attitudes to the use of traditional medicines in pregnancy was also collected. Data were analysed using statistical software SPSS 17.0. Descriptive statistics were used. Chi square tests were used to test for association between independent and dependent variables. RESULTS: Of the 442 patients approached, a total of 357 completed the interview. 41.5% of women used traditional medicine in their current pregnancy. The mean age of the participants was 27 years. Older women and Zulu speaking women were more likely to use traditional medicine in pregnancy (p < 0.05). The most common traditional medicine used was Isihlambezo (63.6%) followed by Umchamo wemfene (19.6%). Traditional medicine was usually ingested in the third trimester. The most common reason for the use of traditional medicine in pregnancy was for a quick delivery (44%). CONCLUSION: The study highlighted that use of traditional medicine in pregnancy amongst postpartum black South African women in Bertha Gxowa hospital was high. Healthcare professionals should have some knowledge of the traditional medicine commonly used by pregnant women in their areas and also inform women about the potential benefits or harms of using traditional medicine in pregnancy.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg In partial fulfilment of the requirements for the Degree of Master of Medicine in Family Medicine